DEVELOPMENT OF SHARIA ACCOUNTING SYSTEM IN THE AGRICULTURAL SECTOR (SITASI) WITH PILOT CONVERSION METHOD - Maryadi Maryadi; Vita Apriliasari; Syanni Yustiani (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
This research was initiated because of a request from the Jaya Makmur Gapoktan, Tonjong District, Brebes Regency which needed an application for its business books. Currently, Gapoktan Tonjong is still doing the bookkeeping manually. Gapoktan Jaya Makmur runs its business in the field of savings and loans with an interest system. However, in practice, this business is more similar to financing with a profit-sharing system that is in accordance with sharia principles. This study develops a sharia accounting system in agriculture that can help Gapoktan Jaya Makmur in keeping its business books. System development includes the stages of system analysis, conceptual design, physical design and implementation. For the implementation phase, the researcher uses the pilot conversion method. The results of this study indicate that there are Gapoktan in Brebes Regency that is still running a business in the field of savings and loans with an interest system. However, there are also those who run a business in the financing sector, which is similar to the mudharabah principle, although it still needs further adjustments. This sharia accounting system in agriculture was developed by default for this type of business financing with the mudharabah system. For Gapoktan who wants to use this application, it is necessary to be given an understanding of the basic concepts of accounting, mudharabah principles, and assistance in the preparation of financial statements.